Perbedaan Intensitas Nyeri Dismenorea Primer Dengan Terapi Nafas Dalam dan Kompres Hangat pada Mahasiswi Universitas Awal Bros - Tinta Julianawati; Eka Fitri Amir; Helly Dewi Yanita (UNIVERSITAS PGRI YOGYAKARTA, 2022)
AbstractDysmenorrhoea is abdominal pain originating from uterine cramps and occurs during menstruation. In Indonesia the incidence of dysmenorrhoea is 64.25% consisting of 54.89% primary dysmenorrhoea and 9.36% secondary dysmenorrhoea. Deep breathing and warm compresses are methods that can reduce menstrual pain in women by relaxing the uterine muscles. This study aims to determine the differences in the intensity of primary dysmenorrhoea pain with deep breathing therapy and warm compresses at the first grade of poltekkes kemenkes malang prodi kebidanan kediri. This study uses two paired sample comparative method. The population in this study was a college student of Poltekkes Kemenkes malang level 1 who had primary dysmenorrhoea, divided into 2 groups, respiratory therapy and warm compresses each 16 students with Probability sampling technique of simple random sampling. Data collection using observation sheets. Data analysis using statistical test of wilcoxon match pairs test and Man-whitney U-test. Result of research on deep breath therapy and warm compress obtained T arithmetic = 0 and T table = 30 then H0 rejected and H1 accepted, it means there is difference Intensity of Primary Dysmenorrhoea Pain before and after given breath therapy in ang warm compresses. Result of calculation by using mann whitney u-test, U arithmetic = 68,5 while value U table for = 43 where error rate 0,05. Then it can be concluded that Ho accepted and H1 rejected. Conclusions from this study there was no difference in the effect of giving deep breath therapy and warm compresses in reducing primary dysmenorrhoea pain. The research suggestion is directed to health workers that to reduce the pain of primary dysmenorrhoea can use deep breathing therapy or warm compresses.Keywords: Primary Dysmenorrhoea, Deep Breathing Therapy, Carm compress